自动变速器平稳结合阀动态特性仿真研究 - 李兴忠; 雷雨龙; 杨成 (Jixie chuandong)
In the process of automatic transmission shift,combination valve can prevent shifting brutally and surface temperature of friction plate rising too fast as well as shift shock and a series of adverse consequences caused by the clutch hydraulic cylinder pressure transiently increased.It plays an important role in improving shift quality.Based on the analysis of the ideal dynamic characteristics of automatic transmission clutch combination during shifting,established the mathematical model and the AMESim simulation model.The dynamic characteristics of the smooth combination valve are simulated and analyzed,and the influences of various structural parameters on dynamic characteristics are compared by simulation.The simulation results can be used as the basis for smooth combination valve design and improvement,and can be used for matching and forecasting the performance of vehicle shifting process.